Teoria da administração escolar no Brasil: contribuições de Lourenço Filho - Barboza, Jaqueline Lima (2017)
Manoel Bergström Lourenço Filho (1897-1970) was one of the pioneers in the development of the theory of school administration in Brazil. Thus, this dissertation has for objective to analyze, your contribution to the theme of the school administration in Brazil, which was of great importance. In order to fulfill this purpose, we developed a search of bibliographic character that is divided into three chapters. In the first, we highlight the major events that marked the history of the school administration in Brazil in the decades of 1920 to 1960, in which we point out that until about 1930 there was a concern in preparing a national theory, because the emphasis fell on the precepts of foreign theories.In the second chapter, we recovered some Lourenço Filho, in order to relate them with the principles of organization and school administration, they are: the training of teachers: The Normal School to the School of Education (collection of articles published between 1922 to 1960); ABC tests: for checking the maturity necessary to learning reading and writing (1933); Trends in brazilian education (1940); The pedagogy of Rui Barbosa (1954) and Comparative Education (1961). And finally, in the third chapter, we present the analysis of the work Organization and school Administration (1963), in which we identify the main concepts regarding the administration of school services in the design of Lourenço Filho. Understanding the education as a social expression, which must develop individual capabilities, we point out that all the author's theoretical production, especially the work Organization and School Administration encourages the preparation of education professionals in order to work in this activity as complex as is education, avoiding improvisation in the actions and in opposition defends the knowledge of reality and educational planning with the prospect of efficiency. Lourenço Filho argued that administer and organize the resources to achieve the desired objectives is essential, stressing that the results in educational activity are not achieved immediate way, however are prospectuses, with getting slow and gradual, why the need to train and prepare professionals to organize and manage the school services to ensure efficient results.